Economists’ Interest in Art and Culture. An International Perspective: Array - Dimitriu (Chișcareanu), Ana-Corina; Hurduzeu, Gheorghe (Acta Universitatis Danubius. Relationes Internationales, 2021)
Art and culture contribute to the economic development of our society. The paper analysis how economists perceived art and culture over time. When it was the moment when the economic literature started writing the importance of the art and culture. The research started with reviewing the specialist literature and updating with the recent interests manifested by the global organizations. The conclusion is that the arts and culture play an important role in society and they became one of the priorities of the international organizations.